Alisher Navoi's Interpretation of Professional and Personal Qualities of Teachers-Coaches in "Mahbub Ul-Qulub" - Iskandarovna, Tosheva Dildora; qizi, Ahmadova Mahbuba Shavkat (International Journal on Integrated Education, 2023)
In this article, the role and importance of education in human perfection is discussed. In this work the teacher’s work his professional and personal qualitis are studied the novel “Makhbub ul –kulub” is a subject of research.